Personality-major congruence among the hearing-impaired students in Malaysian polytechnics - Roslan, Samsilah; Azizan, Che' Rozaniza; Abdullah, Maria Chong; Soaib, Asimiran (Canadian Center of Science and Education, 2015)
Studies in the Person-Environment fit (P-E fit) framework suggested that the greater the match between students’ personality types and their academic major operationalized as personality-major congruence, the more likely they are to succeed. Surprisingly to date, little research has been done on the hearing-impaired population. Thus, this preliminary analysis examined the students’ personality types and the degree of personality-major congruence based on Holland’s theory of vocational personalities and work environment (1997). To provide theoretical focus, gender differences in congruence measure were also investigated. Samples consisted of 26 hearing-impaired students (N=26) undergoing Special Skills Certificate in 4 Polytechnics all across Malaysia. An adapted Malay version of Holland’s Self Directed Search-Form E (SDS-E) was used to measure students’ personality types. Findings on students’ personality-major congruence were descriptively analysed and further discussed. Mann-Whitney U Test was used to analyse differences in personality-major congruence by gender. Findings indicate that gender did not play any significant roles in academic major selection among the hearing-impaired students in Malaysian Polytechnics. However, to certain degree this preliminary analysis provides general information into the largely unstudied question of how the congruence between hearing-impaired students’ personality types and academic major play important role in promoting their educational outcomes. Finally, practical and theoretical considerations were also discussed.